Financing an urban express railway line via real estate development: Hızray (Istanbul) case - Aydın, Emrullah (Graduate School, 2023)
In big cities where population and per capita mobility demand increase rapidly, existing rail systems and other public transportation solutions may be insufficient. In this case, new lines are being developed that will connect the main demand, production, and attraction points of the city at high speed, with high capacity, few stops, and integrated with existing lines. However, difficulties may arise in the financing and construction of these lines, which are generally at the scale of megaprojects. Therefore, different financial resource alternatives are being evaluated. One way that public authorities can fund the development of urban express railways is through the use of development-based land value capture models. These models aim to capture some of the increase in land value that results from the construction of a new rail line or station. For example, a city may require developers to contribute a portion of the increase in land value to the construction and operation of a new rail line. This can help to offset the costs of the rail project and ensure that it is financially sustainable. In this thesis, a literature review was conducted on the effects of rail system lines on land prices and the methods of recovering this value increase, and for this purpose, real estate development issues at first. Before making any contributions to the economic value arising from the combination of land use development and transportation, transit-oriented development (TOD) should be discussed in detail. Therefore, the concept of TOD is explained in the following chapter. Then, the financing methods used for the projects to be developed within the framework of TOD are explained and the development-based land value capture method from Copenhagen, Denmark, and Hong Kong SAR, are expressed. Developed by Istanbul Metropolitan Municipality in Istanbul, Türkiye's largest city with a population of over 16 million, HIZRAY is an urban express rail system line planned to cover a 74,5 km route from Beylikdüzü to Sabiha Gökçen Airport in 50 minutes. Within the scope of this thesis, the public lands around the six stations of HIZRAY were examined, and three real estate projects for Kirazlı, 4. Levent and Kurtköy stations were proposed. It has been revealed that by developing mixed-use projects consisting of hotel, office and commercial areas; approximately 730,284,674 USD sales revenue can be obtained to be used in the financing. In addition, if the office and hotel construction areas are doubled with additional incentives, the expected income reaches 1,203,507,199 USD. The contribution of these properties to the investment cost or other municipal services, similar to the joint development model applied in Hong Kong, is discussed. According to different route and district characteristics, two different process alternatives have been developed, aiming to achieve maximum income or to revitalize urban transformation. Finally, development and improvement suggestions were presented for the HIZRAY Project. In addition to real estate revenues, passenger ticket revenues are expected to make a significant contribution. According to May 2023 values, an average coefficient showing the expensiveness of urban express rail system lines of similar lines in the world compared to other lines in cities is obtained. When a ticket fee of 3 USD per passenger is applied for HIZRAY, it is estimated that approximately 25 billion USD of ticket revenue can be obtained in 32 years with present values. Depending on the pricing policy, it is considered that real estate and other commercial ancillary income can be taken into account in subsidizing ticket prices or facilitating finance mechanisms. Further research can be conducted for forecasting the effects of HIZRAY on real estate prices. At several stations, post-project estimates can be developed with models such as hedonic pricing. In the longer term, for similar lines to be developed in Türkiye and different cities around the world; case projects can be studied to evaluate the existing public lands to contribute to the capital costs.
Bir şehir içi ekspres raylı sistem hattının gayrimenkul geliştirme yoluyla finansmanı: Hızray (İstanbul) örneği
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2023
Keywords: Real estate finance; Gayrimenkul finansmanı; Hafif raylı sistemler; Light rail systems; Project financing; Proje finansmanı; Underground transport; Yeraltı taşımacılığı; Hizray(Istanbul); Hızray (İstanbul)